Knowledge and Attitude of Community Pharmacists Toward Cow Milk Protein Allergy Complications and Treatment in Children: A Cross-Sectional Study in Sudan - Ali ZE; Elameen A; Fadul FA; Babikir RR; Arbab AH (Dove Medical Press, 2024)
Zahraa Elrasheed Ali,1 Abdelrahim Elameen,2 Fatima A Fadul,2 Rawan R Babikir,2 Ahmed H Arbab3 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 3Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Ahmed H Arbab, Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, 11111, Khartoum, Sudan, Tel +249 991893200, Email arbabssn@gmail.comBackground: Cow's milk protein allergy is the most frequent type of food allergy in newborns and young children. It affects numerous body systems. A community pharmacist possessing adequate knowledge and appropriate practices is crucial for the management of the disease.Objectives: : This study aimed to assess the knowledge and attitude of community pharmacists toward the complications and treatment of cow milk protein allergy.Methods: A descriptive cross-sectional study was conducted among 332 randomly selected community pharmacists in the Capital of Sudan (Khartoum state). Data were collected using a validated and internally consistent (Cronbach Alpha = 0.712) self-administered questionnaire Descriptive statistics and Chi-square analysis were conducted using Statistical Package for the Social Sciences version 25.Results: The response rate was 95.8%, and about 47.8% of the population had 1- 5 years of experience as community pharmacists, and 37.4% of them had a post-graduate degree. Only 30.8% of respondents had good knowledge, while 40.6% had poor knowledge, and 28.6% had scored as having fair knowledge of complications of Cow's milk protein allergy. Regarding knowledge toward treatment, 65.1% of respondents had a poor knowledge, 24.5% had fair knowledge, and only 10.4% had good knowledge. Overall, 39.62% of participants had a positive attitude, and 60.38% had a negative attitude toward this disease. Data analysis showed no significant association between the sociodemographic characteristics of respondents and their knowledge and attitude.Conclusion: Community pharmacists in Khartoum State had inadequate knowledge and attitude about the complications and treatment of cow milk protein allergy. As a result, we recommend the implementation of strategies to raise pharmacists' knowledge and attitude.Keywords: community pharmacist, cow milk protein allergy, knowledge, attitude, Sudan